Impact of acute static-stretching on the optimal height in drop jumps - Leonardo A. Pasqua; Nilo M. Okuno; Mayara V. Damasceno; Adriano. E. Lima-Silva; Rômulo Bertuzzi (Motriz: Revista de Educacao Fisica, 2014)
This study analyzed the effect of static stretching on performance during drop jumps. Furthermore, we investigated if a reduction in drop height would compensate the stretching-caused alterations. Ten physically active male subjects performed drop jumps at four different drop heights without static stretching for the optimal drop height determination. After, they performed drop jumps on two drop heights with static stretching previously. The jump height, contact time and reactive strength index were significantly affected by static stretching. However, only the contact time was significantly improved by the reduction in drop height with previous static stretching. Our results suggest that the decrement in performance after static stretching could be partially compensated by a reduction in drop height, which decreases the contact time near a non-stretching jump condition. This can be explained by the lower landing velocity and, possibly, the smaller reduction in the activation of the plantar flexors muscles. In conclusion, the reduction in drop height seems to be interesting after a static stretching session, aiming to expose the athletes to lower impact forces to maintain jump performance.